The Effect Of Profitability, Liquidity, Leverage, And Firm Size On Stock Returns: A Study on Manufacturing Sector Companies Listed on the Indonesia Stock Exchange - Ni Desak Made Amanda Pransiska; Luh Gede Sri Artini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Stock return refers to the income received by investors from their investment in a firm, either directly or through a securities firm. The level of stock return is crucial in investment analysis as it serves as a key indicator for investors in evaluating the performance and profit potential of a stock. This study aims to examine the effect of profitability, liquidity, leverage, and firm size on stock returns in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The sampling technique used was purposive sampling, resulting in a sample of 65 companies. Data analysis techniques employed include descriptive statistics and inferential statistics, processed using IBM SPSS 25. The findings indicate that profitability has a significant positive effect on stock return, liquidity has a significant positive effect, leverage has a significant negative effect, and firm size also has a significant positive effect on stock return. The implications of this study are expected to provide empirical contributions regarding the influence of these variables on stock returns and to offer managerial insights and additional references for corporate decision-making aimed at increasing stock returns. Keywords: stock return, profitability, liquidity, leverage, firm size